Kinerja Layanan Universitas Islam Indonesia Diukur dengan Pendekatan Balanced Scorecard - Joko Susilo (Unisia, 2007)
This paper aims to measure performance measurement of Islamic University of Indonesia by balanced scorecard approach. The balanced scorecard, a performance and strategic management system, has been adopted in for-profit organizations with success and its application in the public sector is explored in this study. Accordingly, the paper uses a survey to measure and analyse a stakeholders’s perception about UII’s performance. Respondent of this study are student, employee, and lecturer of this university. The questionares are proposed with four perspective of balanced scorecard approach.The findings of the study indicate how, in different ways, stakeholders are fully satisfy with performance served by UII. Respondent students, in general, have confidence in the quality of the UII’s performance. Respondent employees and lectures are satisfy in perspective of operating efficiency, inno- vation and change, and employee performance. In the last of this paper, we design model balanced scorecard for UII based on result of survey. Kaywords: Balanced Scorecard, Performance Measurement, Stake- holders.